Reflections on the Cuban missile crisis - Garthoff, Raymond L. (Washington, D.C. : Brookings Institution, 1987)
The book combines an analysis - with new materials and new insights - of the origination, unfolding, and consequences of the Cuban Missiles Crisis with the reflections of a participant and the findings of a scholar studying the Soviet view of the crisis and its significance.
Includes bibliographical references and index.
kjo 17/01/2019
Loans
Keywords: Cuban Missile Crisis, 1962.; International relations